EVIDENCE FOR DISTINCT GENETIC EFFECTS ASSOCIATED WITH RESPONSE TO 35% CO2. Issue 3 (24th January 2013) - Roberson‐Nay, Roxann; Moruzzi, Sara; Ogliari, Anna; Pezzica, Elettra; Tambs, Kristian; Kendler, Kenneth S.; Battaglia, Marco
<x xml:space="preserve">Abstract</x> Background Carbon dioxide (CO2) hypersensitivity represents an individual difference response to breathing CO2 enriched air. People with a history of panic attacks or panic disorder are particularly prone to anxious response, suggesting that CO2 hypersensitivity is a robust risk marker of panic spectrum vulnerability. Methods Twin pairs (n = 346) from the general population‐based Norwegian NIPH Mental Health Study completed a measure of anxiety before and after vital capacity inhalation of 35% CO2 air and before and after inhalation of regular air. Three hypotheses regarding genetic factors for CO2 hypersensitivity were examined: (1) a single set of genetic risk factors impacts anxiety before exposure to CO2 and these same genes constitute the only genetic influences on anxiety in response to CO2, (2) the genetic effects on pre‐CO2 anxiety are entirely different from the genetic effects on anxiety in response to exposure to CO2 (i.e., new genetic effects), and (3) pre‐CO2 anxiety influences anxiety in response to CO2 as well as unique genetic factors that become activated by respiratory stimulation. Results Our results support the latter hypothesis for response to 35% CO2, with additive genetic and unique environmental factors best fitting the data. Evidence of new genetic effects was observed, accounting for 20% unique variance in post 35% CO2 anxiety response. New genetic effects were not observed for anxiety ratings made post regular air where only preregular air anxiety ratings explained significant variance in this outcome. Conclusions These data suggest that there are distinct genetic factors associated with responsivity to respiratory stimulation via 35% CO2.